The Influence of Work Discipline and Motivation on Employee Performance - Harsono, Yhonanda (IJESS International Journal of Education and Social Science, 2024)
This study aims to determine the effect of discipline and work motivation on employee performance at the Meteorology, Climatology and Geophysics Center Region II, South Tangerang City. This study uses quantitative method with an associative approach. The sampling technique used saturated sampling and the sample in this study was 82 respondents. Multiple data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results showed that work discipline has a positive and significant effect on performance with a tcount of 13.332 > ttable of 1.664 and a significant value of 0.000 <0.050. Work motivation has a positive and significant effect on performance with a tcount of 12,600 > ttable 1.664 and a significant value of 0.000 <0.050. Discipline and Work Motivation simultaneously have a positive and significant influence on employee performance with a Fcount of 116.286 > Ftable of 3.112 and a significant value of 0.000 <0.050.